Aplikasi Penyewaan Lapangan Olahraga Berbasis Web Pada Sport Center XYZ - ., Ozmar; Fernando, Lukas; Lee, Francka Sakti; Andry, Johanes Fernandes (Jurnal Sains dan Teknologi (JSIT), 2025)
The rapid and dynamic growth of information technology has compelled organizations to migrate toward online services to streamline operations, create agility, and support data‑driven decision making. Sport Center XYZ, a local facility‑rental provider, still relies on fully manual procedures for court reservations, employee scheduling, and financial documentation. These paper‑based workflows regularly generate data‑entry mistakes, misplaced receipts, and delayed reports, which collectively diminish service quality and operational efficiency. This research designs and develops an integrated web‑based information system that supports real‑time court booking, automated resource allocation, and instant transaction reporting. A qualitative methodology, comprising field observation, stakeholder interviews, and literature review, underpins the requirement elicitation phase. System construction follows the Waterfall model: requirements analysis, object‑oriented development based on UML‑driven design by using Code Igniter Framework, and black‑box testing to verify functional compliance. Deployment results indicate that reservation processing time is reduced dramatically, and comprehensive financial statements can be produced on demand. These accomplishments not only smooth daily operations but also provide management with accurate, timely information for strategic planning. The study concludes that adopting a web information system is an effective solution for modernizing manual sport‑facility operations and can be adopted by similar organizations which plan to elevate performance and customer satisfaction, potentially replicable in diverse contexts worldwide.